O autorstwie tekstów audialnych w teatrze radiowym - Pawlik, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The article discusses the problem of authorship in radio dramas. It focuses on reviewing previous research on this issue and, at the same time, offers suggestions for approaching a dilemma: who is more the author of a given audio text – the scriptwriter or the director? The solutions proposed in the article are based on previous research in the field of cinematography and theatre, two areas which are relatively close to the radio theatre.